The impact of 10-valent pneumococcal vaccine introduction on invasive disease in Fiji - R. Reyburn; E.J. Tuivaga; F.T. Ratu; E.M. Dunne; D. Nand; J. Kado; K. Jenkins; L. Tikoduadua; A. Jenney; B.P. Howden; S.A. Ballard; K. Fox; et al. (Elsevier, 2022)
Summary: Background: In 2012, Fiji introduced the 10-valent pneumococcal conjugate vaccine (PCV10). We assessed the impact of PCV10 on invasive pneumococcal disease (IPD), probable bacterial or pneumococcal meningitis (PBPM), meningitis and sepsis 3-5 years post-introduction. Methods: Laboratory-confirmed IPD and PBPM cases were extracted from national laboratory records. ICD-10-AM coded all-cause meningitis and sepsis cases were extracted from national hospitalisation records. Incidence rate ratios were used to compare outcomes pre/post-PCV10, stratified by age groups: 1-23m, 2-4y, 5-9y, 10-19y, 20-54y, ≥55y. To account for different detection and serotyping methods in the pre-and post-PCV10 period, a Bayesian inference model estimated serotype-specific changes in IPD, using pneumococcal carriage and surveillance data. Findings: There were 423 IPD, 1,029 PBPM, 1,391 all-cause meningitis and 7,611 all-cause sepsis cases. Five years post-PCV10 introduction, IPD declined by 60% (95%CI: 37%, 76%) in children 1-23m months old, and in age groups 2-4y, 5-9y, 10-19y although confidence intervals spanned zero. PBPM declined by 36% (95%CI: 21%, 48%) among children 1-23 months old, and in all other age groups, although some confidence intervals spanned zero. Among children <5y of age, PCV10-type IPD declined by 83% (95%CI; 70%, 90%) and with no evidence of change in non-PCV10-type IPD (9%, 95%CI; -69, 43%). There was no change in all-cause meningitis or sepsis. Post-PCV10, the most common serotypes in vaccine age-eligible and non-age eligible people were serotypes 8 and 23B, and 3 and 7F, respectively. Interpretations: Our study demonstrates the effectiveness of PCV10 against IPD in a country in the Asia-Pacific of which there is a paucity of data. Funding: This study was support by the Department of Foreign Affairs and Trade of the Australian Government and Fiji Health Sector Support Program (FHSSP). FHSSP is implemented by Abt JTA on behalf of the Australian Government.